Disrupting program evaluation and mixed methods research for a more just society : the contributions of Jennifer C. Greene - Hall, Jori N.; Boyce, Ayesha; Hopson, Rodney K. (Evaluation and society., 2023)
While women have influenced the fields of program evaluation and mixed methods research, their contributions are rarely acknowledged. In this edited volume, we recognize the contributions Jennifer C. Greene made to evaluation and mixed methods, focusing on how she disrupted traditional ways methods are conceptualized and implemented. We aim to provide a range of perspectives on how Greene disrupted social science theory, methodology, and training through her commitment to the values of democracy, diversity, and dialogue. Accordingly, the volume makes explicit how Greene democratized social science inquiry and training by emphasizing inclusive, culturally responsive, and educative theories, methods, and pedagogical practices. Second, it clarifies how her commitment to diversity supported scholars from diverse disciplinary backgrounds and cultures (within and beyond the United States) and validated often ignored perspectives on phenomena or experiences. And third, it showcases how her commitment to dialogue opened spaces for non-traditional methodological approaches that engage, communicate, and disseminate program evaluation and mixed methods work. Taken together, the first-hand accounts presented in this volume offer a historical perspective and practical guidance on program evaluation and mixed methods conceptualization, implementation, and training.